Deterioration of the subjective financial well-being during the coronavirus pandemic: a latent transition analysis (2023)
The authors seek (1) to identify the profiles of subjective financial well-being (SFWB) of bank customers before and during the coronavirus disease 2019 (COVID-19) pandemic, (2) to analyze the transition to profiles of lower SFWB during the pandemic and (3) to identify the factors driving such transitions.